Evaluation of porcine T lymphocytes following West Nile virus vaccination - Ostrander, Nicole Elizabeth (My University, 2026)
Japanese encephalitis virus (JEV) is a foreign zoonotic flavivirus of significant concern to the United States (U.S.) swine industry. Currently, there are no approved veterinary vaccines or treatments for JEV in the United States. In contrast, West Nile virus (WNV), a related flavivirus and zoonotic pathogen of concern, does have approved commercial equine vaccines available. Within the Flaviviridae family, some cross-reactivity exists between these viruses, as JEV and WNV share similar structural proteins that often serve as vaccine targets. Cross-neutralizing antibodies between flaviviruses have been documented in both humans and animals following vaccination or natural infection. However, the immune response against JEV infection in swine remains poorly understood, and the mechanisms of protective immunity following vaccination have yet to be investigated. To evaluate potential cross-reactive T-cell immunity, we analyzed CD4+, CD8+, and CD4+CD8+ double-positive T lymphocyte populations within peripheral blood mononuclear cells (PBMCs) isolated from swine vaccinated with commercial equine WNV vaccines. PBMCs were stimulated in vitro with WNV and JEV, and T cell activation was assessed through phenotypic characterization of naïve, central memory, and effector memory subsets. We then assessed the action of these memory T cells by measuring IFNγ expression. An observed increase in IFNγ expression in response to JEV stimulation suggests that these T cell populations could be capable to contributing to protective immunity against JEV through the IFNγ upregulation of defensive immune mechanisms. The generation of cross-reactive immunity from WNV vaccination could enable leveraging available commercial WNV vaccines to provide cross-protection against JEV in the event of JEV introduction into U.S. swine populations.
Keywords: Memory T cells